Counter Selection Substrate Library Strategy for Developing Specific Protease Substrates and Probes - Poreba, Marcin (Cell Chem Biol, 2016)
Legumain (AEP) is a lysosomal cysteine protease that is a lysosomal cysteine protease that was first characterized in leguminous seeds and later discovered in higher eukaryotes. AEP up-regulation is linked to a number of diseases including inflammation, arteriosclerosis and tumorigenesis. Thus legumain is an excellent molecular target for the development of new chemical markers. We deployed a hybrid combinatorial substrate library (HyCoSuL) approach to obtain P1-Asp fluorogenic substrates and biotin-labeled inhibitors that targeted legumain. Since this approach led to probes that were also recognized by caspases, we introduced a Counter Selection Substrate Library (CoSeSuL) approach that biases the peptidic scaffold against caspases, thus delivering highly selective legumain probes. The selectivity of these tools was validated using M38L and HEK293 cells. We also propose that the CoSeSuL methodology can be considered as a general principle in the design of selective probes for other protease families where selectivity is difficult to achieve by conventional sequence-based profiling.